Menanamkan Nilai Lingkungan dan Komunitas Berkelanjutan melalui Pendidikan Agama Islam - Rida Munfarikhah; Adib Mutohar; Ahmad Yusron Avivi (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Awareness of the importance of environmental conservation and sustainable community development is increasingly pressing amidst increasing global ecological damage. Islamic Religious Education (PAI) has strategic potential in instilling sustainability values ​​through moral, spiritual, and ecological ethical teachings derived from the Qur'an and Hadith. This study aims to analyze how PAI plays a role in shaping environmentally conscious character and encouraging sustainable living practices in both formal and non-formal educational contexts. The method used is a literature study by reviewing various scientific journals, books, and research reports that discuss the integration of environmental and sustainability values ​​in Islamic education. The results of the study indicate that the concepts of khalifah fil ardh, amanah, and himayah al-bi'ah in Islam are a strong foundation for the development of environmental education. PAI can be implemented through the curriculum, the habituation of environmentally friendly behavior, and the strengthening of a school culture based on ecological spirituality. In addition, community-based education such as Al-Qur'an education parks (TPA), majelis taklim, and Islamic boarding schools also contribute to building ecological awareness in the community. This study concludes that Islamic Religious Education (PAI) plays a significant role in instilling sustainable values. However, implementation still requires more integrative, innovative, and contextual pedagogical strategies to address modern environmental challenges. Further research is recommended to develop an Islamic Religious Education (PAI) learning model based on Islamic ecopedagogy that is applicable to educational units.